2011
DOI: 10.1111/j.1574-6941.2011.01053.x
|View full text |Cite
|
Sign up to set email alerts
|

Prokaryotic abundance and 16S rRNA gene sequences detected in marine aerosols on the East Sea (Korea)

Abstract: Modern studies on marine airborne prokaryotes over open seas have been rare. Here, to understand their distribution and composition, aerosol as well as surface seawater samples were collected at three sites in the East Sea. The abundance of airborne prokaryotes was 0.7-1.2 × 10(5) cells m(-3) . Partial sequences of the 16S rRNA gene from the aerosols were dominated by Gammaproteobacteria and Bacteroidetes. Interestingly, the numbers of phylotypes of airborne bacteria were comparable to those of seawater bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
65
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 57 publications
9
65
3
Order By: Relevance
“…Most of the large-size algae and other terrestrial plants were probably deposited along the dust's route (above land) rather than being suspended over long distances and, therefore, were rarely found in our sample. It is possible, however, that aerosols from different origins would contain different amounts of marine/freshwater autotrophic organisms, and particularly small-size cyanobacteria (Cho and Hwang, 2011;Lang-Yona et al, 2014;Seifried et al, 2015). Thus, a more typical atmospheric deposition event coming from the southwest (e.g., Herut et al, 2005) rather than from the northeast (Figure 1) would potentially carry more algae or small-size cyanobacteria, and, therefore, airborne autotrophs could be more abundant than what we have observed in this study.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Most of the large-size algae and other terrestrial plants were probably deposited along the dust's route (above land) rather than being suspended over long distances and, therefore, were rarely found in our sample. It is possible, however, that aerosols from different origins would contain different amounts of marine/freshwater autotrophic organisms, and particularly small-size cyanobacteria (Cho and Hwang, 2011;Lang-Yona et al, 2014;Seifried et al, 2015). Thus, a more typical atmospheric deposition event coming from the southwest (e.g., Herut et al, 2005) rather than from the northeast (Figure 1) would potentially carry more algae or small-size cyanobacteria, and, therefore, airborne autotrophs could be more abundant than what we have observed in this study.…”
Section: Discussioncontrasting
confidence: 55%
“…Indeed, both autotrophic and heterotrophic microbes were delivered with the Syrian aerosol studied here (Figure 2). These include commonly isolated bacteria from marine, freshwater, and terrestrial environments (e.g., Cho and Hwang, 2011;Seifried et al, 2015), as well as from the surroundings of the SEMS (Katra et al, 2014;Rahav et al, 2016a). It should be noted, that based on the 16S rRNA gene, we cannot rule out that in addition to heterotrophic microbes, chemolithotrophic bacteria were also part of the aerosol collection (Gat et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that while the aquatic systems are predominated by Gram-negative bacteria (Moriarty and Hayward, 1982;Giovannoni and Rappe, 2000;Jørgensen et al, 2003), Gram-positive bacteria can be comparatively more important in the terrestrial environment (Janssen, 2006;Lauber et al, 2009). Indeed, Gram-negative bacteria were shown to comprise 83% of bacterial isolates from marine aerosols over the East/Japan Sea (Cho and Hwang, 2011). On the contrary, Gram-positive bacteria were found to be dominant (>75%) in aerosols collected at Newton Creek, located in a densely populated area of New York (Dueker et al, 2012a).…”
Section: D-amino Acids and Bacterial Signature In Dom In Precipitationmentioning
confidence: 96%
“…The conducted studies indicate the presence of considerable amounts of pathogenic bacteria in rainwater flowing over different rooftops as well as those collected directly from air [Cho and Hwang, 2011;Polymenakou et al, 2012]. In early spring season they are, however, much scarcer compared to warmer seasons.…”
Section: Resultsmentioning
confidence: 97%